Effectiveness of Alveolar Opening in Patients with Acute Lung Injury and Concomitant Pneumothorax - Yu. V. Marchenkov; V. V. Izmailov; Ye. M. Kozlova; P. V. Bogomolov (Общая реаниматология, 2009)
Objective: to study the efficiency of a lung opening maneuver in patients with acute lung injury (ALI) and concomitant pneumothorax, who were on biphasic positive airway pressure ventilation (BIPAP) and synchronized intermittent mandatory ventilation. Subject and methods. Seventy-three patients with acute lung injury and concomitant pneumoth-orax resulting from blunt chest trauma were examined. Their condition was an APACHE II of 18—24 scores. After elimination of pneumothorax, an open lung maneuver was made using different modes of lung support 3—5 times daily. Results. The study has shown that BIPAP used in patients with ALI and concomitant pneumothorax reduces the time of pleural cavity drainage, which allows the lung opening maneuver to be applied earlier. The employment of the latter in patients with ALI and pneumothorax permits a prompter recovery of lung function during different types of respiratory support, which is attended by reductions in the number of complications, artificial ventilation, and mortality. When the lung opening maneuver is combined with BIPAP, its efficiency considerably increases. Key words: acute lung injury, pneumothorax, BIPAP, lung opening maneuver.